Giambattista Vico: Grundzüge seiner Philosophie - Otto, Stephan (Urban-Taschenbücher, 1989)
Stephan Otto: "Giambattista Vico". Grundzüge seiner Philosophie. Urban-Taschenbücher, Kohlhammer Verlag, Stuttgart 1989. 152 S., br., 28,- DM